Modified EASIX score on day 7 predicts survival and non-relapse mortality in pediatric acute leukemia undergoing haploidentical stem cell transplantation - Cui, Kai; Zhang, Senlin; Du, Yueke; Wang, Qingwei; Chai, Yutan; Gao, Li; Hu, Yixin; Li, Bohan; Tian, Yuanyuan; Zhang, Yongping; Wu, Shuiyan; Hu, Shaoyan; et al. (Frontiers in Immunology, 2026)
BackgroundThe Endothelial Activation and Stress Index (EASIX) has been validated in adult hematopoietic stem cell transplantation (HSCT) recipients as a predictor of overall survival (OS), non-relapse mortality (NRM), and endothelial-related complications. However, the prognostic significance in children receiving haploidentical donor (HID) transplantation based on myeloablative conditioning (MAC) is still uncertain.MethodPediatric leukemia patients who underwent HID transplantation at the Children’s Hospital of Soochow University between January 2020 and December 2024 were retrospectively reviewed. Based on transplantation dates, patients were assigned to training and validation cohorts. EASIX (lactate dehydrogenase (U/L) × creatinine (mg/dL)/platelet (109 cells/L), sEASIX (excluding creatinine), and m-EASIX (substitutes creatinine with C-reactive protein (mg/dL) were calculated at pre-conditioning, day 0, day 7, day 14, and day 30. All indices were log2-transformed investigate their relevance to clinical outcomes.ResultsIn the training cohort, we stratified patients into groups with high or low D7-m-EASIX expressions, based on the optimal cutoff of 4.1 identified using maximally selected log-rank statistics. In the training cohort, D7-m-EASIX >4.1 was an independent predictor of overall survival (OS, HR:2.35, P = 0.013), relapse-free survival (RFS, HR:1.85, P = 0.047), NRM (HR:3.32, P = 0.009), and was associated with II-IV acute graft-versus-host disease (aGVHD, HR:2.16, P = 0.003) in multivariate analysis. The validation cohort supported these results (OS [HR:6.56, P = 0.005], RFS [HR:3.20, P = 0.030], NRM [HR:5.32, P = 0.040], and II-IV aGVHD [HR:2.57, P = 0.008]).ConclusionD7-m-EASIX is a simple and valuable prognostic biomarker for pediatric leukemia patients undergoing HID transplantation based on MAC.